Terahertz metamaterials for biomolecule sensing based on symmetry-broken unit resonators - Heonseong Ryu; Ji-Hun Kang; Sang-Hun Lee (Results in Physics, 2023)
Terahertz waves have gained attention owing to their potential for various bio-applications, including broadband spectroscopy, imaging, and sensing. For development of practical applications in clinical fields, highly sensitive molecular detection is essential. Notably, the molecular sensitivity of optical sensing can be enhanced by utilizing localized electromagnetic waves in metallic optical resonators. In this study, we theoretically design terahertz (THz) metamaterial sensors based on the Fano resonance, enabling highly sensitive and selective molecular sensing without additional molecular labeling. The metamaterial sensors consisting of symmetry-broken unit resonators are designed to support Fano resonances with strongly localized electromagnetic waves through coupling of the resonators. The key concept behind the design is to match the Fano resonance with the characteristic resonance in the target molecules, leading to pronounced changes in the transmission spectra of THz waves through the metamaterial with the analytes. We numerically demonstrate the sensing performance by considering steroids as the target molecules and explain the sensing mechanism using both temporal coupled-mode theory and FDTD numerical simulations.